An interpretive phenomenological study of women's childbirth experiences in Zambia - Kwaleyela, Concepta Namukolo (2016)
Childbirth holds short and long-term physical and psychological effects for women. Yet, numerous investigations into childbirth have overlooked the delicate interrelated psychological and emotional interplay that women experience, in favour of the physical, such as the outcomes of birth, maternal mortality, and the physical skills of healthcare providers. Although quantitative measures derived from these are important to establish and evaluate maternal health, they are not adequate to explain the complexity of the human experience of childbirth. Without this understanding there is inadequate guidance about how to proceed to achieve the Sustainable Development Goals targeting maternal health.